2015
DOI: 10.1039/c4ta06804a
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermally synthesized CuxO as a catalyst for CO oxidation

Abstract: Hydrothermally synthesized CuxO exhibited improved performance for CO oxidation compared to the hydrothermally synthesized Cu2O, as well as commercial CuO nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…It has been suggested that catalysis over copper oxides is significantly influenced by the surface states and defects . Consequently, a range of successful reports exist for the successful formation of supported or unsupported copper oxides with different morphologies . Since the composition of oxides can affect the surface states and defects and thereby the catalytic properties, methods for manipulating these factors should be developed.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…It has been suggested that catalysis over copper oxides is significantly influenced by the surface states and defects . Consequently, a range of successful reports exist for the successful formation of supported or unsupported copper oxides with different morphologies . Since the composition of oxides can affect the surface states and defects and thereby the catalytic properties, methods for manipulating these factors should be developed.…”
Section: Introductionsupporting
confidence: 86%
“…[23] Consequently,arange of successful reports exist for the successfulf ormation of supported or unsupported coppero xides with differentm orphologies. [24][25][26] Since the composition of oxidesc an affect the surface states and defects and thereby the catalytic properties, methods for manipulating these factors should be developed. To the best of our knowledge, to date there has been no successful attempt for ac ontrolled synthesis of supported copper oxide species.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, it is extremelyu rgent to develop new nanocatalystsw ith ah igh catalytic activity.T he catalytic oxidation of CO is at ypical models ystemu sed to understandh eterogeneous catalysis, therefore, as eries of transition metal (e.g.,M n, Co, Cu, Fe, Ce) oxidesa nd their mixtures have been investigated extensively for CO oxidation. [3][4][5][6][7][8] These studies on the design and synthesis of catalysts are divided into two types:p owder catalysts and monolithic catalysts. For powderc atalysts, Co 3 O 4 and its mixtures have emerged as attractive alternative catalysts because of their low cost, environmental benignity,a nd relatively high catalytic activity for low-temperature CO oxidation, in contrast to precious-metal catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that composite interfaces formed by the CO oxidation reaction and the loaded Cu nanoparticles on the surfaces of pure Cu 2 O improved the ability of oxygen chemisorption. Hence, a correlation can be established between T 50 and OCA, where larger O CA corresponded to lower T 50 , revealing that O CA plays a critical role in the CO oxidation reactions 31…”
Section: Resultsmentioning
confidence: 92%